Social Security : The Story of British Social Progress and the Beveridge Plan - Great Britain. Inter-departmental Committee on Social Insurance and Allied Services; Davison, Ronald C. (Ronald Conway), 1884- (London : G.G. Harrap and Co., 1943)
1943 1943 1940s 3 preliminary leaves, 9-62 pages : illustrations, diagrams 75—85 per cent. of male pensioners at ages 65 to 68 are working and earning good wages in addition to their pensions. That, of course, is largely due to the urgent call for their labour when we are in desperate need of manpower, but at least it is evidence that they are capable of useful work. As regards the proposed retirement condition, there is a real likelihood that if we say in future "no pension without retirement," we shall thereby put a premium on prompter retirement. It might well be wiser to leave the rule of unconditional pensions as it is now, but to raise the ages slightly. In a time of good employment that might be politically possible ; if achieved it would make a large cut in the costs to the nation. Let us remember that the vital needs of the young and virile section of any country, their health and nutrition, should always have clear priority over the claims of the old. This applies particularly to Great Britain, which will inevitably have a rapidly ageing population after this war. (d) Can We Afford It? This is a vague question as applied to our social services as a whole, and it deserves only a vague answer. In fact these services, started since 1906, have amply justified themselves on social grounds. So far they have been a paying proposition, for they have vastly improved the quality of our people. Without them, for instance, we should have been lamentably worse off in this dread war. We could neither have fought so well nor have produced such mighty armaments. The Blitz might have been our undoing. Even the higher costs of more adequate social services in the future should certainly be within our capacity to pay. With a slightly higher level of national productivity the all-in cost of social security should still be under 10 per cent. of our total national income. Nor can this 10 per cent. be regarded as so much extra consumption ; 55 15X/2/566/303